Effect of exposure and withdrawal on lead-induced toxicity and oxidative stress in cardiac tissues of rats (2016)
Lead poisoning continues to pose a serious health challenge and more significantly so in developing countries with ineffective waste disposal systems. Recent efforts at solving lead poisoning issues have seen entire towns being resettled from lead-contaminated areas. This study was designed to investigate whether withdrawal of lead exposure results in a resolution of toxic effects of lead in cardiac tissues. Adult male Wistar rats were exposed orally to lead acetate (PbA) at doses of 0.25, 0.5, and 1.0 mg/ml for 6-week duration, after which one-half was sacrificed and the remaining left for a further 6 weeks without lead treatment. Exposure of rats to PbA produced significant decline (P < 0.05) in the activities of antioxidant parameters, including superoxide dismutase (SOD), glutathione peroxidase (GPx), glutathione-S-transferase (GST), catalase (CAT), and reduced glutathione (GSH), whereas malondialdehyde (MDA) concentration was significantly elevated. Animals from the withdrawal period exhibited a similar pattern of alterations, with a significant (P < 0.05) reduction in GSH, GPx, and SOD and a significant elevation in MDA and H2O2 concentrations. However, GST activity was elevated, whereas CAT activity remained unaltered in the withdrawal period. The results of this study showed that cardiotoxicity indicated by induction of oxidative stress and reduction in antioxidant parameters failed to resolve upon withdrawal of lead exposure in male rats during the period of study.